Wind loads and effects on rigid frame bridges with twin-legged high piers at erection stages. Issue 10 (October 2017) - Han, Y; Chen, Z Q; Hua, X G; Feng, Z Q; Xu, GJ
This article presents a procedure for analyzing wind effects on the rigid frame bridges with twin-legged high piers during erection stages, taking into account all wind loading components both on the beam and on the piers. These wind loading components include the mean wind load and the load induced by the three turbulence wind components and by the wake excitation. The buffeting forces induced by turbulence wind are formulated considering the modification due to aerodynamic admittance functions. The buffeting responses are analyzed based on the coherence of buffeting forces and using finite element method in conjunction with random vibration theory in the frequency domain. The peak dynamic response is obtained by combining the various response components through gust response factor approach. The procedure is applied to Xiaoguan Bridge under different erection stages using the analytic aerodynamic parameters fitted from computational fluid dynamics. The numerical results indicate that the obtained peak structural responses are more conservative and accurate when considering the effect of each loading component on the beam and on the piers, and the roles of different loading components are different with regard to bridge configurations. Aerodynamic admittance functions are source of the important part of the error margin of the analytical prediction method for buffeting responses of bridges, and buffeting responses based on wind velocity coherence will underestimate the results.